Two new species of Okenia (Gastropoda: Nudibranchia: Goniodorididae) from eastern Australia and Tanzania - Rudman, William B. (Zootaxa, 2007)
Two new species of the nudibranch genus Okenia Menke, 1830 (Goniodorididae) are described, one from eastern Australian waters and one from the western Indian Ocean. Okenia atkinsonorum sp. nov. is the third Australian species reported to feed on the bryozoan Pleurotoichus clathratus (Harmer, 1902) and is very similar in external shape and colour to the other two species, O. hallucigenia Rudman, 2004 and O. stellata Rudman, 2004. Okenia rhinorma sp. nov. is reported from Tanzania and the Red Sea. Its body shape and anatomy suggest it is related to the ascidian-feeding group in the genus characterised by O. aspersa (Alder & Hancock, 1845).